Breaking Robert's rules the new way to run your meeting, build consensus, and get results - Susskind, Lawrence, Author; Cruikshank, Jeffrey L. (Oxford New York Oxford University Press, 2006)
Every day in communities across America hundreds of committees, boards, church groups, and social clubs hold meetings where they spend their time engaged in shouting matches and acrimonious debate. Whether they are aware of it or not, the procedures that most such groups rely on to reach decisions were first laid out as Robert's Rules more than 150 years ago by an officer in the U.S. Army's Corps of Engineers. Its arcane rituals of parliamentary procedure and majority rule usually produce a victorious majority and a very dissatisfied minority that expects to raise its concerns, again, at the next possible meeting. This book clearly spells out how any group can work together effectively. After briefly explaining the problems created by Robert's rules, the guide outlines the five key steps toward consensus building, and addresses the specific problems that often get in the way of a group's progress. Appendices include a basic one page "handy guide" that can be distributed at meetings and a case study demonstrating how the ideas presented in the book can also be applied in a corporate context. Written in a non-technical and engaging style, and containing clear ideas and instructions that anyone can understand and use, this one-of-a-kind guide will prove an essential tool for any group desperate to find ways of making their meetings more effective. In addition, neighborhood associations, ad hoc committees, social clubs, and other informal groups lacking a clear hierarchy will find solid advice on how to move forward without resorting to "majority rules" or bickering over who will take leadership positions. This book will change the way you hold meetings forever, paving the way for efficiency, efficacy, and peaceful decision making.
Introduction -- Part 1. Overcoming the tyranny of the majority and other problems associated with Robert's rules of order -- 1.Why break Robert's rules? -- 2. What is consensus? -- 3. Getting the right people to the table -- 4. Assigning tasks and leadership responsibilities -- 5. The importance of facilitation -- 6. Confirming that agreement has been reached -- 7. Crafting "nearly self-enforcing" agreements -- 8. Overcoming the barriers to CBA -- Part 2. The five essential steps in the consensus building approach (CBA). Step 1: Convening -- Step 2: Assigning roles and responsibilities -- Step 3: Facilitating group problem-solving -- Step 4: Reaching agreement -- Step 5: Holding parties to their commitments -- Appendix A. Convincing others to use the consensus building approach--a checklist -- Appendix B. Suggested ground rules -- Appendix C. Being a good facilitator -- Appendix D. General Robert goes to town meeting -- Appendix E. Consensus building in the workplace -- Appendix F. Handy guide to the five essential steps in the consensus building approach (CBA) -- Appendix G. Background readings -- Index.
Includes bibliographical references (p. [216]-217) and index.
Keywords: Group decision making; Consensus (Social sciences); Conflict management